AESTHETIC ASSESSMENT OF THE ORNAMENTAL FORMS OF NOTHERN WHITE CEDAR (Thuja occidentalis L.) AND THEIR USE IN GARDEN AND PARK COMPOSITIONS - Popovych, Vasyl; S, (Journal of Agricultural Sciences (Belgrade), 2023)
As you know, Nothern white cedar (Thuja occidentalis L.) is represented in the world by about 200 ornamental forms, 43 of which were discovered and described in landscaping and nurseries of Lviv. The appearance of the first plantations in Lviv dates back to the 20s of the last century. They were introduced by the professor of the medical institute T. Vilchynskyi, who brought material for cuttings from a nursery in Kurnik (Poland). It was mainly Nothern white cedar and several ornamental forms – columnar and pyramidal.The decorative qualities of these cultivars were established and evaluated in points according to characteristic features: the shape and density of the crown, the color of the needles, the nature of branching, and the features of seed-bearing. These decorative qualities formed the basis of the construction of various elements of garden and park compositions with the participation of tapeworms, alleys, green walls, hedges, boskets, topiaries, and rock gardens. The highest number of points (12) was obtained by 46.4% of ornamental forms, 13-16.3%, 10-9.3%, and 8-11.6%. Cultivars with a distinct regular crown shape received high evaluation points. The options for the spatial arrangement of individuals were proposed and the distance between seating positions was recommended. Taking into account the high plasticity of cultivars and the ability to undergo the formation of crowns, variants of clipped hedges and topiaries were recommended.Several models have been proposed based on the distribution of ornamental groups by their symmetry, silhouettes, alignments, contrasts, colors, density, and sizes. Cultivars are selected for each variant, and their group arrangement is proposed.There are 43 introduced cultivars in our study, each of which has its own number derived from the main alphabetical list. The program "Realtime Landscaping Pro 5" is used for the design of composite groups.According to the consolidated alphabetical list, the distance between individuals in the group is calculated by considering their growth data. The 43 forms have been entered into a computer database, which will assist gardeners in selecting plants for the compositional group envisioned by this project.Nothern white cedar cultivars are suggested for use as solitaries, alleys, green walls, and baskets. Plants with high plastic properties, dense crowns, and thin branches pressed against the trunk are recommended for topiaries. There are ornamental forms of various sizes available for rocky gardens (very small, medium, large, and very large), which can be planted with any of the 43 cultivars.
Keywords: Nothern white cedar (Thuja occidentalis L.), ornamental form, landscaping element, composition, aesthetic assessment